2022
DOI: 10.3390/biom12101458
|View full text |Cite
|
Sign up to set email alerts
|

FDCSP Is an Immune-Associated Prognostic Biomarker in HPV-Positive Head and Neck Squamous Carcinoma

Abstract: Background: Head and neck squamous carcinoma (HNSC) poses a major threat to human life. The role of human papillomavirus (HPV) infection in the initiation and progression of HNSC is becoming more widely accepted. HPV-positive (HPV+) HNSC has shown unique responses to cancer therapies, which may be due to differences in immune cell infiltration. It is critical to determine how the immune responses to HPV in HNSC are regulated. Methods: Transcriptome data of HNSC from The Cancer Genome Atlas (TCGA) and the Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…FDCSP expression was reported to be related to TP53 mutational status and chemokine pathways. High expression of this gene was favorable for the prognosis of patients with HPV+ HNSCC [ 30 ]. JCHAIN, PGLYRP4 and SPINK6 had been reported as protective factors for HNSCC patients, consistent with the results in this study [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…FDCSP expression was reported to be related to TP53 mutational status and chemokine pathways. High expression of this gene was favorable for the prognosis of patients with HPV+ HNSCC [ 30 ]. JCHAIN, PGLYRP4 and SPINK6 had been reported as protective factors for HNSCC patients, consistent with the results in this study [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…HPV-positive samples with high expression of FDCSP are enriched in follicular helper T, memory B cells, CD8+ T cells, memory CD4+ cells and macrophages. It was also observed that elevated FDCSP levels and CD8+ T cell abundance were associated with better prognosis in HPV-positive HNSCC with increasing OS [50].…”
Section: Mrnasmentioning
confidence: 90%
“…Importantly, in our literature review, an NEFH (neurofilament heavy chain) transcript was identified in two studies (Table 1). In one of them, NEFH is part of a molecular signature of eight high-risk genes for decreased survival in patients with HPV-positive HNSCC [45]; while in the second study, high NEFH expression was associated with better OS in HPV-positive HNSCC [50]. However, given that both studies have a limited number of samples and diverse analytical strategies, it cannot be assumed that NEFH is one of the most promising prognostic biomarker candidates in HPV-positive HNSCC, so further evidence to support this claim is required.…”
Section: Mrnasmentioning
confidence: 99%
“…Head and neck cancer is a malignant tumor with a high global incidence, ranking as the sixth most common cancer worldwide [1][2][3]. The occurrence of head and neck cancer is highly correlated with smoking, alcoholism and HPV infection [4][5][6]. Over 90% of head and neck cancers are squamous cell carcinomas [7].…”
Section: Introductionmentioning
confidence: 99%